The Effect of Hydrolysis Time Using Microwave on Bioethanol Production from Sorghum Waste (Sorghum Bicolor L.) - Sefrinus Maria Dolfi Kolo (Program Studi Kimia, Universitas Lambung Mangkurat, 2022)
In this study, the production of bioethanol from sorghum bagasse was carried out to understand the surface morphology of sorghum bagasse before and after hydrolysis, the effect of hydrolysis time using a microwave, and the concentration of inoculum on the ethanol content produced. A total of 10 grams of sorghum bagasse was suspended with 250 mL of 2% H2SO4 solution and then heated using a microwave at a temperature of 150ºC with variations in heating time of 20, 30,40, and 50 minutes. The heated hydrolyzate was analyzed for reducing sugar content using UV-Vis. The morphology of sorghum bagasse before and after hydrolysis was analyzed using SEM and quantitative analysis of fermented ethanol using a pycnometer and GC. The results showed that there were differences in the surface of sorghum bagasse before and after hydrolysis, the highest reducing sugar content was obtained at 30 minutes of hydrolysis, which was 30.4 g/L, and the highest concentration of Saccharomyces cerevisiae was 8% which resulted in 5.325% ethanol content using a pycnometer and 9.05% using GC. Keywords: Sorghum bagasse, Hydrolysis, Microwave, Bioethanol